Hare sobre a falácia naturalista - Prola, Lucas Henrique Tentler (2009)
The aim of this dissertation is to present the criticism of Hare to ethical theories who commit the "naturalistic fallacy". These theories, according to the author, search for a "definition" of value words - words that underpin the majority of moral theories. Hare doubts the possibility of a definition of words like "good", "right, "fair", because he believes that such terms are used to recommend, or not, certain acts, to judge certain acts. In order to examine this fallacy, the author proposes the logical study of value words involved in moral judgments, seeking, reflexively, to clarify the role of words like "good" within the moral discourse. The discussion of the Harean metaethics is divided in three chapters. The first deals with the origin of the term "naturalistic fallacy", expressed initially by Moore, where the author firms its position on the undefinability of "good" and exposes the fallacy committed in the identification of good with natural objects. This chapter has, also, an analysis of the relationship between the definitional problem proposed by Moore and the inference problem of the "Law of Hume." The second chapter is a critique of Hare to naturalistic theories and his defense of the applicability of logic to moral discourse - which he believes is essentially prescriptive - through a review of sentences. In the third chapter criticisms to the vision of Hare on the naturalist theories are exposed, and an analysis of these criticisms is elaborated. After this presentation of the subject, I conclude that Hare has good reason to reject naturalism.